Amelioration of biotic stress by using rhizobacteria for sustainable crop produce - Karabulut, Fadime; Khan, Tahir; Shafi, Nusrat; Parray, Javid A. (Elsevier, 2023)
Plant growth promoting rhizobacteria (PGPR) living on plant roots and promoting plant growth are critical to plant growth. These PGPRs exert their effects by facilitating food intake, helping to counteract pathogen attack, and regulating plant hormone levels. PGPR plays an important role in plant growth through direct action mechanisms such as production of phytohormones, increased iron uptake via iron-chelating siderophores, solubilization of inorganic phosphates, and production of volatile compounds that affect plant signaling pathways and metabolism. In addition, PGPR shows synergistic or antagonistic interactions with rhizosphere microorganisms and soil that indirectly increase or improve plant growth rate. Many biotic stress factors affect the growth and reproduction of PGPR in plants. © 2023 Elsevier Inc. All rights reserved.
Keywords: Biotic flora; Biotic stress; Crops; Rhizobacteria; Sustainable production